Pengaruh Current Ratio, Pertumbuhan Penjualan Dan Return On Equity Terhadap Price Book Value Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Reski Nurlia Sari; Mahfudnurnajamuddin Mahfudnurnajamuddin; Amir Mahmud (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
Abstract This study aims to analyze the effect of Current Ratio, Sales Growth, and Return on Equity on Price Book Value in Pharmaceutical Sub-Sector Companies on the Indonesia Stock Exchange for the 2021-2024 period. The independent variables used in this study are Current Ratio, Sales Growth, and Return on Equity. Meanwhile, the dependent variable is Price Book Value. The sample in this study consisted of 11 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. They were selected based on certain criteria using a purposive sampling method. The analysis used in this study was multiple linear regression, partial t-test, simultaneous t-test (F-test), and determinant test (R²-test) processed using SPSS. The results of this study indicate that the Current Ratio variable has a positive but insignificant effect on Price-to-Book Value in pharmaceutical companies. Sales Growth has a positive but insignificant effect on Price-to-Book Value in pharmaceutical companies. Return on Equity has a positive and significant effect on Price-to-Book Value in pharmaceutical companies. Keywords: Current Ratio, Sales Growth, Return on Equity, Price-to-Book Value